Music-supported motor training after stroke reveals no superiority of synchronization in group therapy - Van Vugt, Floris T.; Ritter, Juliane; Rollnik, Jens D.; Altenmüller, Eckart (Frontiers in Human Neuroscience, 2014)
Background. Music-supported therapy has been shown to be an effective tool for rehabilitation of motor deficits after stroke. A unique feature of music performance is that it is inherently social: music can be played together in synchrony. Aim. The present study explored the potential of synchronised music playing during therapy, asking whether synchronised playing could improve fine motor rehabilitation and mood. Method. Twenty-eight patients in neurological early rehabilitation after stroke with no previous musical background were included. Patients learned to play simple finger exercises and familiar children’s songs on the piano for ten sessions of half an hour. Patients first received three individual therapy sessions and then continued in pairs. The patient pairs were divided into two groups. Patients in one group played synchronously (together group) whereas the patients in the other group played one after the other (in-turn group). To assess fine motor skill recovery the patients performed standard clinical tests such as the nine-hole-pegboard test (9HPT) and index finger-tapping speed and regularity, and metronome-paced finger tapping. Patients' mood was established using the Profile of Mood States (POMS). Results. Both groups showed improvements in fine motor control. In metronome-paced finger tapping, patients in both groups improved significantly. Mood tests revealed reductions in depression and fatigue in both groups. During therapy, patients in the in-turn group rated their partner as more sympathetic than the together-group in a visual-analogue scale. Conclusions. Our results suggest that music-supported stroke rehabilitation can improve fine motor control and mood not only individually but also in patient pairs. Patients who were playing in turn rather than simultaneously tended to reveal greater improvement in fine motor skill. We speculate that patients in the former group may benefit from the opportunity to learn from observation.